Impact of Sudden Stratospheric Warming of 2009 on the Equatorial and Low-Latitude Ionosphere of the Indian Longitudes: A Case Study - Yadav, Sneha; Pant, Tarun K.; Choudhary, R.K.; Vineeth, C.; Sunda, Surendra; Kumar, K. K.; Shreedevi, P. R.; Mukherjee, S. (My University, 2017)
Using the equatorial electrojet (EEJ)-induced surface magnetic field and total electron content (TEC) measurements, we investigated the impact of the sudden stratospheric warming (SSW) of January 2009 on the equatorial electrodynamics and low-latitude ionosphere over the Indian longitudes. Results indicate that the intensity of EEJ and the TEC over low latitudes (extending up to 30Â°N) exhibit significant perturbations during and after the SSW peak. One of the interesting features is the deviation of EEJ and TEC from the normal quiet time behavior well before the onset of the SSW. This is found to coincide with the beginning of enhanced planetary wave (PW) activity over high latitudes. The substantial amplification of the semidiurnal perturbation after the SSW peak is seen to be coinciding with the onset of new and full moons. The response of TEC to SSW is found to be latitude dependent as the near-equatorial (NE) stations show the semidiurnal perturbation only after the SSW peak. Another notable feature is the presence of reduced ionization in the night sector over the NE and low-latitude regions, appearing as an â€œionization hole,â€ well after the SSW peak. The investigation revealed the existence of a quasi 16 day wave in the TEC over low latitudes similar to the one present in the EEJ strength. These results have been discussed in the light of changes in the dynamical background because of enhanced PW activity during SSW, which creates favorable conditions for the amplification of lunar tides, and their subsequent interaction with the lower thermospheric tidal fields.
Keywords: EEJ; Equatorial Electrojet; Ionosphere; TEC; Total electron content; Sudden stratospheric warming; SSW